A review of renewable energy scenarios in Europe : methodological approaches and societal elements amid geopolitical tensions - Mikkola, Olli-Matti; Eerikäinen, Nelli; Höysniemi, Sakari; Luukkonen, Saara; Runko, Panu; Sääskilahti, Lauri; Niinistö, Tuomas; Rikkonen, Pasi (Springer Nature, 2026)
This systematic review focuses on the role of renewable energy in shaping the future of the European energy system. It explores the scientific renewable energy scenarios and offers insights into how broadly European-level scenarios have scanned future energy landscapes and the types of utilised scientific knowledge amid geopolitical tensions. To explore the dimensions of the scenario studies, the analysis applies the PESTE framework, which reflects the results on multidisciplinary three perspectives framework for the energy transition. The results underscore a prevailing positivist paradigm in scenario studies of energy transition, conceptualising it as a future characterised by inevitable advancements in techno-economic drivers while other societal as well as biophysical elements tend to play a minor role. However, it is evident that this approach has not been, and will not be in the future, capable of anticipating implications of geopolitical disruptions of the kind witnessed in recent years, for instance. Consequently, there should be more scenario studies based on disciplinary insights beyond techno-economic drivers to increase the understanding of the future of renewable energy. Indeed, there is still an engagement gap in how to effectively deepen dialogue between different disciplines in scenario studies to best describe the energy transition.
Keywords: energy transition; renewables; scenarios; Europe